THE TAIWANESIANS EMIGRATED FROM THE SOUTHEAST ASIAN ISLANDS: A PHONIC AND HISTORICAL APPROACH - Yu, Chen Hurng (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
The origins and migration routes of Taiwanesian populations have long been a topic of scholarly debate, with various theories suggesting connections to regions in Southeast Asia, mainland China, and beyond. Clarifying these connections is essential for understanding the ethnic and linguistic development of Taiwan’s indigenous peoples and their ties to other Austronesian-speaking communities. This study seeks to explore the phonetic and historical relationships between Taiwanesians and Southeast Asian ethnic groups, especially those from the Philippines, Indonesia, Malaysia, New Guinea, and Vietnam, addressing gaps in earlier migration theories that often overlooked oceanographic conditions and linguistic evidence. To accomplish this, the research applies a comparative phonetic analysis of basic vocabulary across 67 ethnic languages, using data from four historically documented Taiwanesian languages alongside sixteen contemporary ones. The analysis draws on digitized dictionaries and historical sources and incorporates insights from regional linguists and anthropologists to strengthen the comparative approach. The results show notable phonetic similarities between Taiwanesian languages and several languages spoken in the Philippines—such as Hiligaynon, Ivatan, Ilocano, and Tagalog—as well as connections with Indonesian languages like Bugis, Sangir, Toba Batak, and Minangkabau. In contrast, the phonetic overlap with languages from New Guinea is limited, indicating weaker linguistic ties. Historical records, including evidence of ocean currents and oral histories, support the hypothesis of a south-to-north migration pathway that enabled the movement of populations from the Indonesian archipelago and central Philippine Islands toward Taiwan. This research questions previous assumptions that Taiwanesians once spoke early forms of Bahasa Malay or Bahasa Indonesia, instead revealing complex linguistic diversity and migration patterns within the broader Austronesian world. By combining phonetic comparisons with historical context, the study offers new perspectives on the ethnic and linguistic affiliations of Taiwanesian populations. These findings provide a foundation for further interdisciplinary research on Austronesian migration and highlight the value of phonetic evidence as a tool for uncovering ancient population movements and fostering greater cross-regional collaboration in historical linguistics and anthropology.